Tinjauan Kritis terhadap Urgensi Ilmu Jarḥ wa al-Taʿdīl dalam Menilai Kualitas Hadis - Farhan, Rivki Lutfiya (Journal of Hadith Studies, 2022)
This paper offers a critical review of the article “The Urgency of the Science of Jarḥ wa al-Taʿdīl in Determining the Authenticity of Hadith” by Muh. Haris Zubaidillah, Basyrul Muvid, and Srifariyati. The article underscores the crucial role of Jarḥ wa al-Taʿdīl in evaluating hadith authenticity by examining the reliability and credibility of narrators within the chain of transmission (isnād). The authors argue that this discipline forms a key mechanism in hadith criticism, where both isnād (the chain of narrators) and matn (the textual content) are fundamental components in verifying the validity of a hadith. This review applies a library research method with an analytical approach, focusing on the coherence of arguments and the methodological design presented by the original authors. The review appreciates the authors' consistency in affirming the significance of Jarḥ wa al-Taʿdīl as an essential discipline in hadith studies. It also highlights the necessity for hadith scholars to possess competence in this field to determine the acceptability or rejection of transmitted narrations accurately. Additionally, the review commends the authors’ reflective efforts to respond to skeptical perspectives that challenge the reliability of Jarḥ wa al-Taʿdīl as a scientific approach. However, it also notes a critical shortcoming: the article does not sufficiently develop a strong and systematic argument to counter orientalist critiques that question the authenticity of hadith. Strengthening this aspect would enhance the article’s academic contribution and its role in contemporary discourse on hadith criticism.